Frequency of anti- Toxoplasma gondii IgA, IgM, and IgG antibodies in high-risk pregnancies, in Brazil - Fernando Henrique Antunes Murata; Marina Neves Ferreira; Natália Sahyoun Camargo; Gabriela Soria Santos; Lígia Cosentino Junqueira Franco Spegiorin; Aparecida Perpétuo Silveira-Carvalho; Vera Lucia Pereira-Chioccola; Luiz Carlos de Mattos; Cinara Cássia Brandão de Mattos (Revista da Sociedade Brasileira de Medicina Tropical)
Abstract: INTRODUCTION Toxoplasmosis during pregnancy can be severe; thus, it is essential to diagnose the disease via serological tests. METHODS An enzyme-linked immunosorbent assay (ELISA) was used to investigate anti-Toxoplasma gondii immunoglobulin A (IgA), M (IgM) and G (IgG) antibodies in 62 high-risk pregnant women. RESULTS Forty-three (69.4%) women were positive for IgA, 31 (50%) for IgG, and 57 (91.9%) for IgM; 4 (6,5%) were positive for IgA but negative for IgM; 10 (16.1%) were negative for IgA and IgM but positive for IgG. CONCLUSIONS Testing for these antibodies can help diagnose infection in pregnant women, thereby contributing to clinical management.